2016
DOI: 10.1007/s00276-016-1661-6
|View full text |Cite
|
Sign up to set email alerts
|

The linea aspera as a rotational landmark: an anatomical MRI-based study

Abstract: Surgeons should have the R angle measured before performing a distal femoral reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…They found that the linea aspera deviates on average 6.9° laterally at the distal femur, 2.2° medially at the midshaft and 6.9° laterally at the proximal third [27]. Also, Reple et al and Abdelaal et al concluded that preoperatively the orientation of the linea aspera should be assessed in order to avoid a malrotation of the femoral component [25,26]. Although they all used the PCL as a reference, they used a different methodology in measuring the orientation and deviation of the linea aspera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the linea aspera deviates on average 6.9° laterally at the distal femur, 2.2° medially at the midshaft and 6.9° laterally at the proximal third [27]. Also, Reple et al and Abdelaal et al concluded that preoperatively the orientation of the linea aspera should be assessed in order to avoid a malrotation of the femoral component [25,26]. Although they all used the PCL as a reference, they used a different methodology in measuring the orientation and deviation of the linea aspera.…”
Section: Discussionmentioning
confidence: 99%
“…This axis represents the flexion-extension axis of the knee [12,13,[21][22][23][24]. However, recent literature has been questioning the reliability of the linea aspera [25][26][27]. The linea aspera is the longitudinal crest on the posterior side of the femoral diaphysis and consists of a lateral and a medial labium.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the linea aspera version has been proposed as a landmark to assess the rotation of the distal femoral epiphysis in knee arthroscopy. [ 11 ] This is because it lines most of the shaft of the femur, making it a versatile anatomical landmark of the femur to be used for rotational alignment. [ 20 ] One study by Abdelaal et al, [ 20 ] was identified to investigate utility of linea aspera to estimate the femoral anteversion.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the posterior condylar plane, the bi-epicondylar axis, the trochlear groove axis and linea aspera. [ 9 11 ] The linea aspera is the rough, longitudinal, irregular crest that lines most of the shaft of the femur and functions as a muscle attachment site. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation